E-LEARNING FOR LEARNERS’ COMPREHENSION IN LINGUISTICS : A NEED ANALYSIS - Frimadhona Syafri; Zainal Rafli; Emzir Emzir (English Review: Journal of English Education, 2018)
The study focuses a need analysis towards the use of ELENA basis on CALLA Approach as a media in enhancing learners’ comprehension in Introduction to Linguistics course. Universitas Negeri Semarang has website for e-learning that is named ELENA (electronic learning aids). Using e-learning by web to provide information of the course will be real time and interactive. The subjects of the study were learners in fifth semester in academic year of 2016-2017 in English Department in Universitas Negeri Semarang. The semi-structured interview, observation, and descriptive survey were done to gather the data. The data were transcribed, identified, classified, analyzed, and interpreted to gain the answer of the research problem. The problem posed in the research is “To analyze a need analysis towards the use of online learning: ELENA basis on CALLA Approach as a media enhance learners’ comprehension in Introduction to Linguistics course” Based on the overall data analysis and interpretation, a need analysis towards the implementation of ELENA basis on CALLA Approach as a media can provide learners’ comprehension in learning Linguistics concepts. The result showed that; 1) Learners need to gain knowledge at a glance about the scope of Linguistics; 2) Learners need to be stimulated to observe and analyze the development of the language around it; 3) Learners need media and means of communication forums and discussions both offline and online; 4) Learners need to be facilitated with adequate bandwidth and infrastructure for internet use; and 5) Learners are strengthened by e-learning and there are assessments in the use of e-learning. It can be conclude that need analysis is necessary in designing the instructional model, due to it is a process to determine the learners’ needs based on their wants, lacks, and necessities.Keywords: a need analysis, m e-learning, Introduction to Linguistics